Interleukin-6 gene polymorphism (rs1800796) in patient with diabetic nephropathy among Balinese - Gusti Ayu Putu Ratna Wati; Asri Lestarini; Sri Agung Aryastuti; Pande Ayu Naya Kasih Permatananda; Putu Nita Cahyawati (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Background: Diabetic Nephropathy (DN) is the most common complication of diabetes mellitus. Interleukin 6 (IL-6) known as pro-inflammatory cytokine increases extracellular matrix expression and proliferation in DN progression. One single nucleotide polymorphism (SNP) of the Interleukin (IL)-6 gene, rs1800796 play a role in the progression of DN among Asian. Objective: This research seeks to investigate the correlation between IL-6 gene polymorphism (rs1800796) and diabetic nephropathy in individuals diagnosed with type 2 diabetes mellitus (T2DM) among the Balinese population.Methods: This research employed an observational approach through a case-control design involving a total of 60 subjects for each group selected by a simple random sampling method. The occurrence of the rs1800796 polymorphism was identified through polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The genotype and allele distribution acquired in this study were assessed using the chi-square (χ2) test and Hardy-Weinberg equilibrium law.Results: There were no significant differences identified in the occurrence of (DN) based on the genotype or allele distribution of the IL-6 gene rs1800796. Genotype CG-GG had a higher risk of becoming DN with Odd ratio 1.230, but not statistically significant (p=0.577). Allele G with OR 1.198 (p=0.502) was not significant in causing DN. Conclusion: No significant association was identified between IL-6 polymorphism (rs1800796) and diabetic nephropathy in Balinese individuals with type 2 diabetes mellitus. The lack of association could be due to the presence of other haplotypic connections or might require a larger sample size for conclusive results.